2000
DOI: 10.1103/physrevlett.84.151
|View full text |Cite
|
Sign up to set email alerts
|

Whispering Vortices

Abstract: Experiments indicating the excitation of whispering gallery type electromagnetic modes by a vortex moving in an annular Josephson junction are reported. At relativistic velocities the Josephson vortex interacts with the modes of the superconducting stripline resonator giving rise to novel resonances on the current-voltage characteristic of the junction. The experimental data are in good agreement with analysis and numerical calculations based on the two-dimensional sine-Gordon model. 74.50.+r, 05.45.Yv, 85.25.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
1
23
0
2
Order By: Relevance
“…Such resonant steps have been predicted by numerical studies and been experimentally observed in parallel arrays of small Josephson junctions, 6,7 stacks of Josephson junctions, [8][9][10][11][12][13] and two-dimensional Josephson junctions. [14][15][16][17] In this paper, we will show that Cherenkov radiation also occurs in extremely narrow long Josephson junctions. The interest to study fluxon dynamics in long narrow junctions has been recently boosted by the fact that the effective mass of a fluxon, in such junctions, is small enough to observe macroscopic quantum effects.…”
Section: Introductionmentioning
confidence: 99%
“…Such resonant steps have been predicted by numerical studies and been experimentally observed in parallel arrays of small Josephson junctions, 6,7 stacks of Josephson junctions, [8][9][10][11][12][13] and two-dimensional Josephson junctions. [14][15][16][17] In this paper, we will show that Cherenkov radiation also occurs in extremely narrow long Josephson junctions. The interest to study fluxon dynamics in long narrow junctions has been recently boosted by the fact that the effective mass of a fluxon, in such junctions, is small enough to observe macroscopic quantum effects.…”
Section: Introductionmentioning
confidence: 99%
“…The interest to annular long JJ's stems from the great potential they offer for fundamental studies of dynamical properties of solitons, such as, e.g., emission of the Cherenkov radiation. 5,6 A challenging problem for the theory is quantum soliton dynamics in long JJ's, which has been recently observed in experiment at ultralow temperatures. 7 On the other hand, annular JJ's offer applications in cryoelectronics, such as sources of highly coherent microwave radiation 4 and radiation detectors.…”
Section: Introductionmentioning
confidence: 99%
“…13 Other studies relied on fluxon trapping in the course of cooling the system below the critical temperature T c of the superconducting electrodes. [3][4][5][6]14,15 However, the latter technique does not provide for reproducible results, and requires heating of the junction to high temperatures. Moreover, trapped fluxons generated in such a manner get often pinned by Abrikosov vortices, which may be trapped in the electrodes in the course of cooling below T c .…”
Section: Introductionmentioning
confidence: 99%
“…9, the excitation of whispering-gallery-type electromagnetic modes by a moving fluxon in an annular Josephson junction was found in Ref. 10. The fluxon dynamics in exponentially tapered Josephson flux-flow oscillator was studied in Ref.…”
Section: Introductionmentioning
confidence: 99%